Old or new occupants of energy rehabilitated buildings. Two different approaches for hierarchizing group of buildings. (October 2017) - Ferrante, Patrizia; Peri, Giorgia; Rizzo, Gianfranco; Scaccianoce, Gianluca; Vaccaro, Valentina
Highlights: Limited public finances need prioritization criteria to energy retrofit buildings. In these criteria the users of the rehabilitated buildings should be considered. A criticism about the energy class as ranking criterion is arisen. The role of the true energy behaviour against the standardized one is discussed. Significant differences between two prioritized orders of 23 buildings are found. Abstract: Public Administrations are frequently entitled to intervene in building stocks with energy rehabilitation actions. Unfortunately, the monetary budget at their disposal is generally limited and, consequently, a prioritization criterion is needed to optimize its allocation. The classification of the building energy performance is increasingly used by Public Administrations for this purpose. Here we argue that a proper prioritization criterion should depend upon the potential subjects to which the rehabilitated buildings are given back. If the energy rehabilitation is conducted on buildings that will be assigned to new dwellers, it would be preferable to use the energy class – which is based on a standardized energy consumption – because a change of the building users will occur with a consequent plausible change of the building energy usage profile. Instead, if same dwellers will occupy the retrofitted building, a criterion based on a usage profile – that is actually the one established by these occupants – seems to be more appropriate. The priority orders of 23 buildings of the Sicilian stock, obtained using their energy class and real energy consumption, are presented and compared. Results show at which extent these two rankings differ, thus warning Public Administrations about prioritization criteria to adopt.